Resistensi Antibiotik pada Salmonella Isolat Sapi Bakalan Asal Australia yang Diimpor Melalui Pelabuhan Tanjung Priok Jakarta (ANTIBIOTIC RESISTANCE OF SALMONELLA ISOLATES FROM AUSTRALIAN IMPORTED FEEDER CATTLES THROUGH TANJUNG PRIOK PORT JAKARTA) - Kurniawati, Anindya; Lukman, Denny Widaya; Wibawan, I Wayan Teguh (Jurnal Veteriner; Vol 17 No 3 (2016), 2016)
Importation of feeder cattle from farms constantly using antibiotics in feed could result in the occurrenceof antibiotic resistant bacteria. A study was therefore conducted to investigate the possible use antibioticsand the antibiotic resistance of commensal Salmonella sppagainst several antibiotics. Salmonella spp.bacteria (n=50)were isolated from 100 samples of feeder cattlesfaeces. Total of 50 Salmonella spp. isolateswere subjected for Salmonella spp. examination and the isolated Salmonella spp. was tested for theantibiotic resistance using 10 antibiotics (ampicillin, cephalotin, erythromycin, tetracycline, streptomycin,chloramphenicol, trimethoprim, trimethoprim-sulfamethoxazole, nalidixic acid, and enrofloxacin) usingdisk diffusion method on Muller-Hinton agar following Clinical and Laboratory Standards Institute (CLSI)guidelines for interpretation. The isolated Salmonella showed resistance towards erythromycin 98%,ampicillin 34%, streptomycin 22%, nalidixic acid 8%, cephalotin 6%, tetracycline 4%, and chloramphenicol2%. There was no resistance against enrofloxacin, trimethoprim, and trimethoprim-sulfamethoxazole. Salmonella spp. bacteria derived from imported feeder cattle which have been resistant to antibiotics arepotential for spreading the antibiotic resistant bacteria to other susceptible animals. Such bacteria canalsotransfer the antibiotic resistant gene to other bacteria in Indonesia which ould be a potential threatfor public and animal healths.
Keywords: antimicrobial resistance, Salmonella spp., beef cattle